Congregational Membership, Church Purity, and Presbyterian and Congregationalist Polemics During the Puritan Revolution - Chung, Youngkwon (Tyndale bulletin, 2019)
During the revolutionary decade of the 1640s, intra-Puritan conflict over ecclesiology, or the theological issue of church government, dominated the ecclesiastical landscape of England. Owing to the leading Puritans’ lack of support for complete separatism as an ecclesiological alternative, the conflict pitted mainly the Presbyterians against the Congregationalists. This divergence of opinion over ecclesiastical system of governance has fascinated historians. Yet what this article finds is that, somewhat surprisingly, church purity, which was an issue closely linked to church system of governance and emerged as another highly contested theme vis-à-vis ecclesiology among contemporary polemicists, has not received the attention it deserves. Both Presbyterian and Congregationalist polemicists discoursed at length about the imperative of setting up pure churches, safeguarding the purity of churches from spiritual contamination, and maintaining the religious integrity of both its members and divine ordinances; yet, in many important ways, they differed over the precise means and mechanisms to achieve such a state of purity and integrity for the life of the church. It is hoped that a detailed examination of this theme of church purity as discoursed and debated by the Presbyterians and Congregationalists will add fresh perspectives on earlier works on religious conflict amongst the Puritans as it unfolded over the course of the revolutionary decade of the 1640s as well as the subsequent decade.